Nanotechnologies in neurosurgery: current concepts and development perspectives - Tsymbalyuk, V. I.; Kremets, C. G. (Ukrainian Neurosurgical Journal, 2009)
Nanomedicine is a field of medical science that deals with diagnostics, treatment and prevention of diseases and injuries, relieving pain, human health preservation and improvement using molecular tools and knowledge about human body structure on molecular level. The goal of nanomedicine is to study and apply nanotechnological developments in practical medicine. It is rapidly developing science. As neurosurgery is one of the most «technocratic» and advanced medical field, so nanotechnological developments will be used widely in neurosurgery and this will lead to appearance of fundamentally new diagnostic and treatment modalities in the nearest future. In this review the major problems of nanotechnologies in neurosurgery and heir future perspectives are briefly elucidated.